Pengaruh Reliability, Responsivenes, Assurance, Emphathy dan Tangible Terhadap Kepuasan Pasien di RSUD Geneng - Ayu Wulansari; Adrie Frans Assa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the influence of service quality dimensions, namely tangible, reliability, responsiveness, empathy and assurance on patient satisfaction at the Geneng Regional General Hospital (RSUD). Based on analytical observational research with a cross-sectional approach, data was collected from 110 patients who met the criteria at Geneng District Hospital from December 2024 to January 2025. The analytical method used was the t test to test the significance of the relationship between each dimension of service quality and patient satisfaction. The research results show that the tangible dimension has a significant influence on patient satisfaction with a tcount of 2.687 > ttable 1.982 and a significance of 0.008 < 0.05. The responsiveness dimension also has a significant influence with a t value of 2.360 > t table 1.982 and a significance of 0.020 < 0.05. Empathy shows a significant influence with a t value of 4.768 > t table 1.982 and a significance of 0.000 < 0.05. The assurance dimension has a significant influence with a t value of 2.938 > t table 1.982 and a significance of 0.004 < 0.05. Meanwhile, the reliability dimension does not show a significant influence with a t value of 0.677 < t table 1.982 and a significance of 0.500 > 0.05. Overall, the results of this study emphasize the importance of managing the physical aspects of hospitals, increasing the ability of medical personnel to provide quick responses, paying attention to patients' emotional needs, and ensuring competence in creating satisfactory services. This research can contribute to Geneng Hospital in designing strategies to improve patient satisfaction and the overall quality of health services.